(untitled) (Research, Society and Development, 2021)
This paper aims to analyze privacy in the information society through the Brazilian general law of data’s protections; To purchase this perspective, the paper was structured from three themes: the new contours that build the privacy, trough the values ​​brought by the Federal Constitution of 1988, and the modifications from the paradigm of information society with the results of technological developments; the modern system of personal data protection after the Law n. 13.709 / 2018, which contains new boundaries to the adequate protection of fundamental rights of freedom and privacy in the guardianship of personal data displayed through digital platforms; and, lastly, it is proposed the debate about the resemblance between the dystopia written in the book 1984 by George Orwell and the reality that prevails in the modern society.